Experimental study on lightweight concrete using pumice aggregate. (2021) - Karthika, R.B.; Vidyapriya, V.; Nandhini Sri, K.V.; Merlin Grace Beaula, K.; Harini, R.; Sriram, Mithra
Abstract: Concrete is the commonly used manufactured building material in the world, owing to its usefulness and relatively low cost. One of the disadvantages of conventional concrete is its high self-weight. This heavy self-weight of concrete will result in uneconomical structural material. To decrease the self-weight of concrete, the coarse aggregate is replaced partially by lightweight aggregate. This is known as lightweight concrete having low density, reduction of dead load and to increase thermal insulation. There are two types of lightweight aggregate - natural lightweight aggregate and artificial lightweight aggregate. One of the most commonly available natural lightweight aggregate called pumice aggregate is used as a replacement for coarse aggregate. Pumice aggregate is used because of its low density than conventional coarse aggregate, and it is easily available. Lightweight concrete is prepared by partially replacing the coarse aggregate with pumice aggregate by 50%, 80% & 100%. The conventional concrete and pumice lightweight aggregate concrete is made by using mix M30 with Conplast SP430 admixture. The mechanical and durability properties of conventional concrete and pumice lightweight aggregate concrete are compared by conducting various destructive and non-destructive tests and favorable replacement is found.